Conceptualizing the effectiveness of flood risk information with a socio-hydrological model: A case study in Lower Kelani River Basin, Sri Lanka - Perera, Chamal; Nakamura, Shinichiro (Frontiers in Water, 2023)
In rapidly changing human-flood systems, dynamic models can assist with system thinking, policy-making, and response. Previous research has shown that flood memory is important for better responses during disasters. To date, socio-hydrological research has primarily focused on memory accumulation after flood events and the related dynamics and feedback mechanisms. Notably, the impact of risk information has not yet been considered in any modeling exercise. Accordingly, this study improved upon the socio-hydrological model (SHM) by incorporating the impact of risk information on collective memory and associated dynamics. Probable flood maps were used to assess the response of a floodplain community from the Lower Kelani River Basin, Sri Lanka, via two interview surveys conducted at a 6-month interval. The surveys were conducted under two categories: A – after distributing maps and conducting awareness sessions, and B – after showing and distributing flood maps. The results showed that the flood maps helped to improve the risk perception of floodplain communities. Of the two categories, the memory decay process was slower for Category A. Furthermore, the SHM application showed that flood damage in the study area could be reduced by 10–30% when flood maps were distributed, and awareness sessions were conducted at 1–5-yr intervals.